Fish and Crustacean Communities and Fish Length-Weight Relationship of Lutong River, Miri, Sarawak, Malaysia - Lee, Nyanti; Teck, Yee Ling; Grinang, Jongkar (IDOSI, 2012)
This study was carried out to determine the composition and diversity of fish and crustacean fauna in Lutong River, Sarawak and length-weight relationship of major fish species caught. A total of 33 species of fish and crustacean belonging to 28 genera and 23 families were recorded from the study area. Thirty-nine percent of the number of individuals caught was from the family Ambassidae, 15% from Penaeidae, 10% from Portunidae, 8% from Mugilidae, 6% from Megalopidae, 4% from Scatophagidae and 3% from Centropomidae. Many of the individuals caught were small-sized individuals indicating the role of the river, to a certain extent as a nursery area. However, compared to other less disturbed areas such as Paloh mangrove, the number of species and families recorded in Lutong River were only 47 and 58% respectively of those recorded in Paloh mangrove likely due to the lack of abundance of food as detritus were less in Lutong River. The values of parameter b of the length-weight relationships for nine fish species ranged from 2.65-3.10 with only three species showing positive allometric growth. The low number of species and low fish species with positive allometric growth were possibly due to the impacts of human settlement and petroleum industry.